2014
DOI: 10.1016/j.chembiol.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Chemoenzymatic Synthesis of Glycoproteins for Deciphering Functions

Abstract: Summary Glycoproteins are an important class of biomolecules involved in a number of biological recognition processes. However, natural and recombinant glycoproteins are usually produced as mixtures of glycoforms that differ in the structures of the pendent glycans, which are difficult to separate in pure glycoforms. As a result, synthetic homogeneous glycopeptides and glycoproteins have become indispensable probes for detailed structural and functional studies. A number of elegant chemical and biological stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
149
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 153 publications
(184 reference statements)
0
149
0
1
Order By: Relevance
“…Thus, methods that can lead to the production of structurally well defined, homogeneous glycoforms of antibodies are highly desirable for both functional studies and for the development of better antibody-based therapeutics. In parallel to the attempt to control glycosylation through host glycosylation pathway engineering (14 -20), a chemoenzymatic glycosylation remodeling method, which involves endoglycosidase-catalyzed deglycosylation and subsequent transglycosylation of intact antibodies, has been emerging as a promising approach to obtain homogeneous antibody glycoforms (21). We have initially shown that the Fc glycans of recombinant IgG-Fc domain could be remodeled through the enzymatic deglycosylation-transglycosylation steps under the catalysis of an appropriate endoglycosidase, including Endo-A 2 and Endo-D, without the need of denaturing the proteins (22)(23)(24).…”
mentioning
confidence: 99%
“…Thus, methods that can lead to the production of structurally well defined, homogeneous glycoforms of antibodies are highly desirable for both functional studies and for the development of better antibody-based therapeutics. In parallel to the attempt to control glycosylation through host glycosylation pathway engineering (14 -20), a chemoenzymatic glycosylation remodeling method, which involves endoglycosidase-catalyzed deglycosylation and subsequent transglycosylation of intact antibodies, has been emerging as a promising approach to obtain homogeneous antibody glycoforms (21). We have initially shown that the Fc glycans of recombinant IgG-Fc domain could be remodeled through the enzymatic deglycosylation-transglycosylation steps under the catalysis of an appropriate endoglycosidase, including Endo-A 2 and Endo-D, without the need of denaturing the proteins (22)(23)(24).…”
mentioning
confidence: 99%
“…Recent reviews have highlighted advancements in the study of glycosyl transferases, 75 glycotherapies, 76 and methods for preparing glycoproteins for performing structure-function studies. [77][78][79] Wu and coworkers developed a technology for the evaluation of LacNAc levels in histology sections. Taking advantage of the promiscuity of a1,3-fucosyltransferase in binding modified monosaccharides, the researchers were able to transfer an alkyne-labeled fucose to LacNAc-decorated glycans within formalin-fixed paraffin-embedded tissue samples, which were subsequently detected with a fluorescent click partner.…”
Section: Glycan Remodelingmentioning
confidence: 99%
“…Many elegant chemical and biochemical strategies have been explored for making homogeneous glycoproteins and mimics, including total chemical synthesis with native chemical ligation (13-17), chemoselective ligation (18, 19), chemoenzymatic synthesis (20 -24), and glycosylation pathway engineering in host expression systems (25-28). As part of these efforts, we have attempted to develop a chemoenzymatic method for construction of complex N-glycopeptides and glycoproteins that is based on the transglycosylation activity of a class of endo-␤-N-acetylglucosaminidases (the endoglycosidases that hydrolyze N-glycans of glycoproteins) for convergent native ligation of preassembled glycans and GlcNAc-peptide/ protein (20,23,24). The success of this approach relies on the availability of novel endoglycosidase-derived glycosynthase mutants that are devoid of hydrolysis activity but can use the highly activated glycan oxazolines as substrates for transglycosylation.…”
mentioning
confidence: 99%